Acute physiological and performance responses to repeated sprints in varying degrees of hypoxia - Bowtell, J. L.; Cooke, K.; Turner, R.; Mileva, K. N.; Sumners, D. P. (Journal of Science and Medicine in Sport, 2014)
Objectives: Our aim was to determine the effects of different inspired oxygen fractions on repeated sprint performance and cardiorespiratory and neuromuscular responses, to construct a hypoxic dose response. Design: Nine male well-trained multi-sport athletes completed 10 × 6 s all-out running sprints with 30 s recovery in 5 conditions with different inspired oxygen fraction (FIO2: 12%, 13%, 14%, 15%, 21%). Methods: Peak running speed was measured in each sprint and electromyography data were recorded from m. vastus lateralis in parallel with heart rate and blood oxygen saturation. Cardiorespiratory response was assessed via breath by breath expired air analysis and muscle oxygenation status was evaluated via near infrared spectroscopy. Results: In parallel with the higher heart rate, minute ventilation, blood lactate concentration, and muscle deoxygenation; lower blood oxygen saturation, pulmonary oxygen uptake and integrated EMG (all p < 0.05) were registered in all hypoxic conditions, with the greatest changes from baseline observed during the 13% trial. However, fatigue index and speed decrement were significantly greater only during the 12% vs 21% trial (p < 0.05). Conclusions: Physiological responses associated with performing 10 × 6 s sprints interspersed with 30 s passive recovery was incrementally greater as FIO2 decreased to 13%, yet fatigue development was significantly exacerbated relative to normoxia (FIO2: 21%) only at the 12% FIO2.